Advanced output of silicone molds in vacuum casting processes by polyamide 12 powder supplementation. Issue 17 (22nd November 2019) - Wortmann, Martin; Hoffmann, Andrej; Frese, Natalie; Heide, Alexander; Brikmann, Johannes; Brandt, Niklas; Menzel, Michell; Gölzhäuser, Armin; Moritzer, Elmar; Hüsgen, Bruno
ABSTRACT: Vacuum casting of polyurethane in silicone molds is a widely used method for prototype replication and holds great potential for application in small batch production. Products produced in this way offer extremely good shape accuracy even in the nanometer range and high surface quality, as well as flexible material properties that are convenient for serial production. In this work, we present a new method for increasing the feasible output of silicone casting molds in vacuum casting processes. By supplementation of polyamide 12 powder, which is a waste product of the selective laser sintering process, to the silicone rubber the maximum output of the casting molds could be increased by up to 38.5% while the amount of new silicone used has been substituted by up to 20%. Both generic silicone samples and representative silicone molds have shown that with increasing polyamide content, aging characteristics decrease as the output increases. The improvement was quantified by comparative weight, hardness and thermogravimetric measurements. As surface energy and roughness measurements as well as extensive casting experiments have shown, the silicone surface and thus the product surface remains unimpaired. GRAPHICAL ABSTRACT: